A psychological perspective on augmented reality in the mathematics classroom - Bujak, Keith R.; Radu, Iulian; Catrambone, Richard; MacIntyre, Blair; Zheng, Ruby; Golubski, Gary (Computers and education, 2013)
Physical objects and virtual information are used as teaching aids in classrooms everywhere, and until recently, merging these two worlds has been difficult at best. Augmented reality offers the combination of physical and virtual, drawing on the strengths of each. We consider this technology in the realm of the mathematics classroom, and offer theoretical underpinnings for understanding the benefits and limitations of AR learning experiences. The paper presents a framework for understanding AR learning from three perspectives: physical, cognitive, and contextual. On the physical dimension, we argue that physical manipulation affords natural interactions, thus encouraging the creation of embodied representations for educational concepts. On the cognitive dimension, we discuss how spatiotemporal alignment of information through AR experiences can aid student's symbolic understanding by scaffolding the progression of learning, resulting in improved understanding of abstract concepts. Finally, on the contextual dimension, we argue that AR creates possibilities for collaborative learning around virtual content and in non-traditional environments, ultimately facilitating personally meaningful experiences. In the process of discussing these dimensions, we discuss examples from existing AR applications and provide guidelines for future AR learning experiences, while considering the pragmatic and technological concerns facing the widespread implementation of augmented reality inside and outside the classroom. ► Augmented reality has a great, but relatively unexplored, potential for education. ► Using psychological constructs, we analyze existing systems and suggest guidelines. ► Constructs consider the physical, cognitive and contextual dimensions of learning. ► Guidelines are offered from a psychological view to improve AR in the classroom. ► There are pragmatic and technological concerns facing widespread implementation.